Menyoal Keterjalinan Orang Hidup dan Mati menurut Tradisi Batak dan Ajaran Huria Kristen Batak Protestan - Ricky Pramono Hasibuan; Nixcon Simanungkalit; Nelson Situmeang; Ricky Pramono Hasibuan (Universitas Negeri Medan, 2021)
This research aims to discuss the teachings of the Protestant Batak Christian Church (HKBP) and the Toba Batak about the relationship between the living and the dead. Batakness believes the dead still have a relationship with the living, while HKBP denies it. To reconcile these two doctrines, we will reinterpret “the communion of saints” phrase in the Apostolic Creed, which always presents as one of the main elements in the liturgy of HKBP. We argue that the “communion of saints” is an association of all believers, not only cross-geographical (trans spatial) but also cross-age (trans temporal). The relation of the living and the dead in the association is not direct but via Christ. Therefore, the trans temporality of the communion is evidence of the connectedness of the living and the dead.